2019
DOI: 10.1007/s10560-019-00622-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences (ACEs) and Risk of Childhood Delays in Children Ages 1–5

Abstract: Adverse childhood experiences (ACEs) have been found to be important contributors to negative health outcomes throughout the lifespan. Birth to 5 years represent a critical period for brain development impacting cognitive, emotional, and social competencies. This study aims to determine the association between overall ACE score and risk of developmental, social, or behavioral delay in a sample of children ages 1-5 years from the National Survey of Children's Health (N = 21,139). Approximately 1 in 4 (27.3%) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…There are some potential points of alignment between these two domains. For example, the impact of cumulative ACEs on developmental, social and behavioral delays may provide bridges between epidemiological and developmental approaches to childhood risk and resilience (e.g., Cprek et al, 2020). A better integration of ACEs with developmental psychopathology, however, will require far more dialogue in the future between these largely separate disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…There are some potential points of alignment between these two domains. For example, the impact of cumulative ACEs on developmental, social and behavioral delays may provide bridges between epidemiological and developmental approaches to childhood risk and resilience (e.g., Cprek et al, 2020). A better integration of ACEs with developmental psychopathology, however, will require far more dialogue in the future between these largely separate disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Using measures of timing and duration of ACE exposure during years 1, 3, and 5, they found that intermittent adversity in early childhood was associated with a nearly fourfold increase in the odds of internalizing problems and a nearly fivefold increase in the odds of externalizing problems at age 9 compared to children with no/low adversity. Other studies have shown that children who are exposed to ACEs within the first five years of life are more likely to suffer from mental illnesses (Schalinski et al 2016) and have developmental, social, and behavioral delays (Cprek et al 2020; Guinosso et al 2015; Jimenez et al 2017) in middle childhood and late adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the exposure of ACEs, the accumulation, timing, and duration of early ACEs may be particularly important to later life outcomes. Indeed, recent studies suggest that exposure to ACEs early at the age of 5 years or younger are associated with negative cognitive, physical health, and behavioral outcomes across the life course (Cprek et al, 2020; Hunt et al, 2017; McKelvey et al, 2017). Moreover, early exposure to frequent or prolonged ACEs can increase the risk of toxic stress responses in young children weakening the overall growth and functioning of the brain, which can lead to lifelong problems in learning, behavior, and physical and mental health (Bucci et al, 2016; McEwen & McEwen, 2017).…”
Section: Introductionmentioning
confidence: 99%